The Effect of the Urban Ambient Air Pollution Mix on Daily Mortality Rates in 11 Canadian Cities - Burnett, Richard T. (Can J Public Health, 1998)
Objective: Determine the risk of premature mortality due to the urban ambient air pollution mix in Canada. Methods: The number of daily deaths for non-accidental causes were obtained in 11 cities from 1980 to 1991 and linked to concentrations of ambient gaseous air pollutants using relative risk regression models for longitudinal count data. Results: Nitrogen dioxide had the largest effect on mortality with a 4.1% increased risk (p<0.01), followed by ozone at 1.8% (p<0.01), sulphur dioxide at 1.4% (p<0.01), and carbon monoxide at 0.9% (p=0.04) in multiple pollutant regression models. A 4% reduction in premature mortality was attributed to achieving a sulphur content of gasoline of 30 ppm in five Canadian cities, a risk reduction 12 times greater than previously reported. Conclusions: Ambient air pollution generated from the burning of fossil fuels is a risk factor for premature mortality in 11 Canadian cities.